Anti-Cancer Effects of Pristimerin and the Mechanisms: A Critical Review - Li, Jia-jun; Yan, Yan-yan; Sun, Hong-mei; Liu, Yun; Su, Chao-yue; Chen, Hu-biao; Zhang, Jian-ye (Frontiers in Pharmacology, 2019)
As a quinonemethide triterpenoid extracted from species of the Celastraceae and Hippocrateaceae, pristimerin has been shown potent anti-cancer effects. Specifically, it was found that pristimerin can affect many tumor-related processes, such as apoptosis, autophagy, migration and invasion, vasculogenesis, and drug resistance. Various molecular targets or signaling pathways are also involved, such as cyclins, reactive oxygen species (ROS), microRNA, nuclear factor kappa B (NF-κB), mitogen-activated protein kinase (MAPK), and PI3K/AKT/mammalian target of rapamycin (mTOR) pathways. In this review, we will focus on the research about pristimerin-induced anti-cancer activities to achieve a deeper understanding of the targets and mechanisms, which offer evidences suggesting that pristimerin can be a potent anti-cancer drug.